2022
DOI: 10.1155/2022/6732972
|View full text |Cite
|
Sign up to set email alerts
|

Occludin Promotes Adhesion of CD8+ T Cells and Melanocytes in Vitiligo via the HIF-1α Signaling Pathway

Abstract: Loss of melanocytes induced by activated CD8+ T cells is the pathological hallmark of vitiligo. Melanocyte-specific CD8+ T cells are recruited to the skin via chemokines, thereby releasing perforin, granzyme, and other cytotoxic substances that destroy the melanocytes. However, the mechanism of CD8+ T cells to adhere to melanocytes is unknown. Previous transcriptome sequencing results published by our group showed that the occluding (OCLN) gene was significantly upregulated in CD8+ T cells from skin lesions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Zou et al. found that fibroblasts from vitiligo patients significantly express occludin, suggesting its potential function in the continuous retention of CD8 + T cells within the lesions ( 62 ). Consequently, the secretion of ECM by fibroblasts exhibits regional variations, potentially contributing to the disparate incidence of vitiligo across different anatomical regions.…”
Section: The Role Of Dermal Fibroblasts In Autoimmune Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zou et al. found that fibroblasts from vitiligo patients significantly express occludin, suggesting its potential function in the continuous retention of CD8 + T cells within the lesions ( 62 ). Consequently, the secretion of ECM by fibroblasts exhibits regional variations, potentially contributing to the disparate incidence of vitiligo across different anatomical regions.…”
Section: The Role Of Dermal Fibroblasts In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Instead, the expression of collagen type IV, fibronectin, elastin, and adhesion components was considerably lower in the lesional skin of non-segmental vitiligo (NSV) patients (61). Zou et al found that fibroblasts from vitiligo patients significantly express occludin, suggesting its potential function in the continuous retention of CD8 + T cells within the lesions (62). Consequently, the secretion of ECM by fibroblasts exhibits regional variations, potentially contributing to the disparate incidence of vitiligo across different anatomical regions.…”
Section: Dermal Fibroblasts In Vitiligomentioning
confidence: 99%